Analisis Kandungan Protein dan Serat pada Bakso Ayam Fortifikasi Tepung dan Ekstrak Edamame (Glycine max (L) Merrill) - Indis, Nadhifah Al (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 10 No 1 (2025)DO - 10.24843/JITPA/2025.v10.i01.p04, 2025)
Edamame ( Glycine max (L) Merrill ) is a vegetable green bean widely cultivated in Jember Regency, and is an export commodity. Edamame has a high protein content of 30-40%, fat 20%, carbohydrates 33%, and fiber 6%. Edamame is also rich in vitamins and minerals. However, the utilization of edamame in Indonesia is still limited to snacks and boiled green beans. This research aims to utilize edamame reject export sold at a low price to be processed into flour and protein extract. This flour and protein extract are used as food additives to increase the protein and fiber content of chicken meatballs. The experimental design was designed using a CRD consisting of 5 treatments and 2 repetitions. Treatments are distinguished based on the percentage of protein extract and edamame flour addition. The method used for protein extraction is MAE, sensory analysis with hedonic test, protein analysis with Kjeldahl, crude fiber analysis with Chesson Datta, and statistical analysis with one way ANOVA followed by DMRT (?=0.05). Based on the research conducted, the highest protein content of 19.330% and crude fiber of 5.955% were obtained from treatment BA.01 (15% edamame flour and 0% tapioca), but this variation was less favored by the panelists. The best treatment was obtained from BA.03 (5% edamame flour and 10% tapioca) with a protein content of 15.196% and crude fiber of 4.245%, and it was favored by the panelists (average score for taste parameter is 3.48; aroma 3.59; color 3.37; texture 3.41, and overall preference 3.59). Keyword: edamame, chicken meatballs, sensory, protein, and crude fiber